Clinical and demographic factors associated with stimulant use disorder in a rural heart failure population. (1st December 2021) - Hendricks, Brian; Sokos, George; Kimble, Wes; Dai, Zheng; Adeniran, Olayemi; Osman, Mohammed; Smith, Gordon Stephen; Bianco, Chris
Abstract: Background: Heart failure is becoming increasingly common among patients under 50 years of age, particularly in African Americans and patients with stimulant use disorder. Yet the sources of these disparities remain poorly understood. This study identified key demographic and clinical factors associated with stimulant use disorder in a largely rural heart failure patient registry. Methods: Patient records reporting a diagnosis of heart failure between January 2008 and March 2020 were requested from West Virginia University Hospital Systems (n=37, 872). Odds of stimulant use disorder were estimated by demographic group (age, race, sex), insurance carrier, and clinical comorbidities using logistic regression. Results: Multivariable regression analysis identified higher odds of stimulant use disorder among Black/African Americans (1.95 [1.32, 2.77]) and patients who report drinking one or more alcoholic drinks per week (2.23 [1.72, 2.88]). Lower odds of stimulant use disorder were identified among patients with hypertension (0.59 [0.47, 0.73]), or diabetes (0.65 [0.52, 0.81]).. Likewise, lower odds of stimulant use disorder were noted among females, patients older than 30 years of age and those not enrolled in Medicaid. Conclusion: These results highlight the alarming extent to which Medicaid enrollees, Black/African Americans, people aged 18–24 and 25–44, or persons with a past alcohol use disorder diagnosis are associated with stimulant use disorder among heart failure populations living in largely rural areas. Additionally, they emphasize the need to develop policies and refine clinical care that affects this vulnerable population's prognoses. Highlights: Retrospective records reviews conducted in a large rural heart failure registry. Disparities in prevalence of stimulant use disorder among heart failure patients by race, age, and socio-economic status. Risk factors identified inform stimulant use disorder patient profiles in rural heart failure populations.